The effectiveness of the employment act 1955 (act 135) in protecting the rights of foreign workers in term of maximum working hours and compliance of wages / Mohd Asni Mansor, Raja Norliana Raja Mohamed Tamimi, Nurul Liyana Mohammad Nasir. - Mansor, Mohd Asni; Raja Mohamed Tamimi, Raja Norliana; Mohammad Nasir, Nurul Liyana (2009)
In Malaysia, the number of foreign workers has grown from year to year. Today more than 1.3 million foreign workers are employed in various sectors. The supply of foreign workers in Malaysia seems to exceed the demand. These bring about problems, and in order to get money, the foreign workers are willing to do any job at any cause, as long as they receive payment. By this, they merely sign any contract of service with any place that would hire them without understanding the content of the contract. Nowadays, many problems arise when the foreign workers are being manipulated and lose their rights of employment. Two aspect of prevailing infringement of the foreign workers employment rights will be scrutinizes none working in excess of the permitted 12 hour per day and non- compliance with the wages stated in the contract of service. The later in particular has lead many foreign workers to other unhealthy even illegal activities in Malaysia just make end meet.